The impact of resumption of former top executives on stock prices: an event study approach - Yang, Tai-Ning (Journal of Business Economics and Management, 2013)
This study explored the impact of resumption of former top executives on stock prices based on market model for the listed corporations in Taiwan stock market. Top executives nowadays confront great challenges in acquiring new corporate accounts to meet agreed targets and drive rapid, profitable growth. Accordingly, corporations commonly decide to reinstate former top executives since their managerial experience is expected to improve corporate performance. The aim of this study is to provide practical guidelines for companies that are considering such decisions and favorable information that can help investors to adjust their portfolios in response to such potential decisions.